Trauma-informed care (TIC) - Touch Mercer, Gina (Henry Stewart Talks, 2023)
Health impact of trauma, Sources and manifestations of trauma, Key principles of trauma-informed care, Toxic stress, Individual trauma, The 4F model, Complex PTSD, Adverse childhood experiences (ACEs)